Paris School Semiotics : Volume I: Theory. - Perron, Paul (John Benjamins Publishing Company, 1989)
It has often been claimed that the aim of semiotics is to establish a general theory of systems of signification. However, as Jean-Claude Coquet notes in a recent collection of essays, what distinguishes one school of semiotics from another is the initial definition given of sign. If, for certain semioticians, the sign is first of all an observable phenomenon, for the Paris School it is first of all a construct and this point of departure has crucial theoretical and practical consequences. The essays appearing in these two volumes are representative of recent work carried out by members of thi.